Different roles of Indian Ocean Basin and Dipole modes in tropical Pacific climate variability - Yingying Zhao; Fengfei Song; Daoxun Sun; Lu Dong; Antonietta Capotondi (npj Climate and Atmospheric Science)
Abstract Indian Ocean (IO) variability, including the Indian Ocean Basin (IOB) mode and the Indian Ocean Dipole (IOD) mode has been suggested to influence Tropical Pacific (TP) variability. On the other hand, variability in the tropical Pacific, especially the El Niño Southern Oscillation (ENSO) has also been presented as a major driver of both IOB and IOD. The relative importance of these coupled feedbacks is still debated. Here, we use a Linear Inverse Model (LIM) capable of selectively including or excluding IO-TP coupling to evaluate the relative roles of the IOB and IOD modes on TP variability, and the preferred timescales of those impacts. Our findings reveal a reduction in TP interannual variability (~40%) and a substantial increase in central TP low-frequency variability (>6 years) in the absence of IO coupling. Specifically, both the IOB and IOD contribute significantly to TP interannual variance. IOB dynamics substantially damp central TP low-frequency variability, while the IOD exhibits negligible impacts on the TP at low-frequencies. We further assess the relative importance of internal IO dynamics versus that induced in the IO by the Pacific in shaping tropical Pacific variability. Our findings indicate that internal IO dynamics predominantly impact Pacific interannual variance, while the Pacific’s influence on the IOB, rather than internal IOB dynamics, is the primary factor dampening Pacific low-frequency variance. This study deepens our understanding of the intricate coupled IO-TP interactions.